Using a randomized controlled trial to develop conservation strategies on rented farmlands. Issue 4 (24th May 2021) - Weigel, Collin; Harden, Seth; Masuda, Yuta J.; Ranjan, Pranay; Wardropper, Chloe B.; Ferraro, Paul J.; Prokopy, Linda; Reddy, Sheila
Abstract: Addressing the environmental impacts of large‐scale agriculture requires innovative approaches to conservation program design and evaluation. We used a randomized controlled trial and a sample of 2225 landowners in the Mississippi River Basin to test a new conservation program that targets a growing but overlooked population—nonoperating landowners (NOLs). To spur adoption of conservation practices on farmland rented out by NOLs, the program provided NOLs with ready‐to‐use lease language and a financial incentive. The program's design was informed by field work, the behavioral science literature, and the social science literature on barriers to conservation on farmland. We cannot detect an effect on conservation practices from the lease language or the incentive. The take‐up rate for the incentive was one‐tenth the expected rate based on NOL responses to a hypothetical offer in a survey. The results underscore the importance of assessing program performance by rigorously testing programs in real conservation settings.